Conditions and Characteristics of the Emergence and Development of the Social Organization Tupac Amaru in Argentina (Revista Rupturas, 2018)
This is a socio-cultural analysis on the social organization Tupac Amaru in northwest Argentina. It seeks 1) to unravel the factors that led to the emergence of this populist movement, and 2) to interpret different dimensions on their demands and the way they build their ties within the social organization. This characterization seeks to bring light to the factors that led to its massive emergence and productive burst, as well as its subsequent stigmatization and conviction. As a result we consider the organization to be a catalyst of regional historical conflicts; and understand its demands by the intersectionality of its militants. This research is based on a multi-sited ethnography
Keywords: Social movements; populism; intersectionalities